Nanoparticle-mediated targeting of PGC-1α reveals critical metabolic pathways in bladder cancer metastasis - Zhenghua Liu; Peng Xin; Weiwei Wu; Mingyue Jin; Yang Du; Yuanjun Jiang; Tao Liu; Hao Zhang (Communications Biology)
Abstract Metastatic bladder cancer is characterized by its aggressive behavior and complex molecular mechanisms that remain largely undefined. This study explores the therapeutic potential of targeting peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) using liposomal nanoparticles to deliver PGC-1α siRNA to bladder cancer cells. We employed comprehensive transcriptomic, proteomic, and metabolomic analyses to investigate the impact of PGC-1α silencing. Our in vitro results demonstrate that targeting PGC-1α significantly impairs mitochondrial function and disrupts energy metabolism, affecting critical pathways such as glycolysis and the citric acid cycle, as well as altering mRNA nuclear export. In vivo experiments in animal models show that nanoparticles loaded with si-PGC-1α effectively reduce lung metastasis, indicating a significant impact on metastatic progression. These findings highlight PGC-1α as a key regulator of metabolic reprogramming in metastatic bladder cancer and suggest that its inhibition could serve as a promising therapeutic strategy. By elucidating the role of PGC-1α in cancer metabolism, this study provides new insights into the molecular underpinnings of bladder cancer metastasis and offers potential avenues for developing targeted therapies aimed at the metabolic vulnerabilities of this malignancy.